Athermal electric field effects in flash sintered zirconia. (19th May 2021) - Dong, Jian; Biesuz, Mattia; Sglavo, Vincenzo M.; Kermani, Milad; Su, Xiaojia; Saunders, Theo; Hu, Chunfeng; Grasso, Salvatore
ABSTRACT : We propose an innovative methodology to quantify the dependence of grain growth with respect to current density during flash sintering of zirconia (3YSZ) (field set under a nominal current limit of 150 mA mm −2 . This was achieved by using a notch (0.5 mm deep and 1.5 mm wide) located in the middle of a dog-bone specimen, allowing an uneven current distribution (ranging from 3 to 670 mA mm −2 ) while maintaining a fairly homogeneous temperature (1420–1500 °C). Microstructure observations nearby the notch tip confirmed localised overheating. The modelling approach decoupled thermal and electrical field effects identifying the long questioned athermal electric field effects in flash sintering. Increased current density seems to weakly restrain grain growth, to accelerate densification, to promote defects healing (i.e. notch, cracks and pores) and inter-particle bond formation. These results could rationalise the athermal effects occurring during FS and flash joining.